Ehrlichia phagocytophila genogroup rickettsiae in ixodid ticks from California collected in 1995 and 1996. - Barlough, J E (1997)
A total of 1,246 ixodid ticks collected in 1995 and 1996 from seven California counties were examined for the presence of Ehrlichia phagocytophila genogroup rickettsiae by using a nested PCR technique. Of 1,112 adult Ixodes pacificus Cooley and Kohls ticks tested, nine pools, each containing five ticks, were positive (minimum percentage of ticks harboring detectable ehrlichiae, 0.8%). Positive ticks were limited to four of the seven counties (Sonoma, El Dorado, Santa Cruz, and Orange). In Santa Cruz County, three positive pools were identified at the home of an individual with prior confirmed human granulocytic ehrlichiosis. In El Dorado County, positive ticks were found at sites where cases of granulocytic ehrlichiosis in a horse and a llama had recently occurred. Among 47 nymphal I. pacificus ticks collected in Sonoma County, one positive pool was identified. Fifty-seven adult Dermacentor occidentalis Marx and 30 adult D. variabilis Say ticks, collected chiefly in southern California, were negative. These data, although preliminary, suggest that the prevalence of E. phagocytophila genogroup rickettsiae in ixodid ticks of California may be lower than in cognate vector populations (i.e., I. scapularis Say = I. dammini Spielman, Clifford, Piesman, and Corwin) in the eastern and midwestern United States.